Prácticas de enseñanza de lógica matemática en Inicial II en la Unidad Educativa Particular Trilingue Helmut Wahlmuller - Sánchez Meneses, Erika Patricia (2016)
This research has as a purpose to find out how teachers perform their pedagogical practices when teaching mathematics to 4 years old children. The study is based on an analysis of field, whose overall objective is to describe the development of teaching practices in the field of mathematics logical relationships in everyday school life. The investigation was done with children from “Unidad Educativa Particular Trilingüe “Helmut Wahlmüller”. Nowadays we can see that the teachers who work in the field of mathematics logical relationships in elementary schools, do not have the methodological and didactic practices that this requires, since most of the time his teaching is not scheduled, it is improvised which reduces the value of their schooling. It shows that the teacher does not support his/her classroom work on proper planning and according to the age of the children, that is to say, they don’t design in advance: objectives, resources and assessment strategies and simply complies with the activities that are already written in textbooks leaving aside their creativity and enthusiasm for teaching. The research results provide us with the lack of appropriate due process of teaching / learning in the field of mathematical logic relationships in the group of children referred methodological strategies.